Exposure to large-scale social and behavior change communication interventions is associated with improvements in infant and young child feeding practices in Ethiopia - Kim, Sunny S.; Rawat, Rahul; Mwangi, Edna M.; Tesfaye, Roman; Abebe, Yewelsew; Baker, Jean; Frongillo, Edward A.; Ruel, Marie T.; Menon, Purnima (Public Library of Science, 2016)
Optimal breastfeeding (BF) practices in Ethiopia are far below the government's targets, and complementary feeding practices are poor. The Alive & Thrive initiative aimed to improve infant and young child feeding (IYCF) practices through large-scale implementation of social and behavior change communication interventions in four regions of Ethiopia. The study assessed the effects of the interventions on IYCF practices and anthropometry over time in two regions-Southern Nations, Nationalities and Peoples Region and Tigray. A pre- and post-intervention adequacy evaluation design was used; repeated cross-sectional surveys of households with children aged 0-23.9 mo (n = 1481 and n = 1494) and with children aged 24-59.9 mo (n = 1481 and n = 1475) were conducted at baseline (2010) and endline (2014), respectively. Differences in outcomes over time were estimated using regression models, accounting for clustering and covariates. Plausibility analyses included tracing recall of key messages and promoted foods and dose-response analyses. We observed improvements in most WHO-recommended IYCF indicators. Early BF initiation and exclusive BF increased by 13.7 and 9.4 percentage points (pp), respectively. Differences for timely introduction of complementary foods, minimum dietary diversity (MDD), minimum meal frequency (MMF), minimum acceptable diet (MAD), and consumption of iron-rich foods were 22.2, 3.3, 26.2, 3.5, and 2.7 pp, respectively. Timely introduction and intake of foods promoted by the interventions improved significantly, but anthropometric outcomes did not. We also observed a dose-response association between health post visits and early initiation of BF (OR: 1.8); higher numbers of home visits by community volunteers and key messages recalled were associated with 1.8-4.4 times greater odds of achieving MDD, MMF, and MAD, and higher numbers of radio spots heard were associated with 3 times greater odds of achieving MDD and MAD. The interventions were associated with plausible improvements in IYCF practices, but large gaps in improving children's diets in Ethiopia remain, particularly during complementary feeding.